A Faculty Development Session or Resident as Teacher Session for Didactic and Clinical Teaching Techniques; Part 1 of 2: Engaging Learners with Effective Didactic Teaching - Megan Boysen-Osborn; Shannon Toohey; Michael Gisondi; Margaret Wolff (eScholarship Publishing, University of California, 2016)
Audience: This workshop is intended for faculty members in an emergency medicine (or other) residency program, but is also appropriate for chief residents and medical student educators, including basic science faculty. Introduction: Faculty development sessions are required by the Accreditation Council for Graduate Medical Education and enhance the learning environment within residency programs. Resident as teacher sessions are important in helping residents transition from junior learners to supervisors of medical students and junior residents. Part I of this two-part workshop introduces learners to effective techniques to engaging learners during didactic sessions. Objectives: By the end of this workshop, the learner will: 1) describe eight teaching techniques that encourage active learning during didactic sessions; 2) plan a didactic session using at least one of eight new teaching techniques for didactic instruction. Methods: This educational session is uses several blended instructional methods, including team-based learning (classic and modified), the flipped classroom, audience response systems, pause procedures in order to demonstrate effective didactic teaching techniques.